Unpacking Medium Effects on Social Psychological Processes in Computer-mediated Communication Using the Social Relations Model. Issue 2 (23rd March 2018) - Liao, Wang; Bazarova, Natalya N; Yuan, Y Connie
Abstrat: This article introduces the social relations model (SRM) to unpack medium effects on social psychological processes. Although such effects have been theorized at group, dyadic, and individual levels separately, some of them can be concurrently analyzed as medium moderation on SRM components. Drawing on existing theories of computer-mediated communication (CMC), we map SRM components onto social psychological processes susceptible to medium effects: (a) "group mean" and "consensus" onto group social integration, (b) "uniqueness" and "dyadic reciprocity" onto relationship development, and (c) "assimilation" and relations between ingroup and outgroup SRM components onto social identity processes. We also summarize the SRM analytics and scenarios of medium moderation, and illustrate the key analytical procedures for adopting the SRM for CMC research.